A Pronunciation Error Analysis of an Experienced and a Novice English Lecturer at Poltekkes Bhakti Pertiwi Husada Cirebon - Siti Fatimah; Teni Hadiyani; Kurnihayati Kurnihayati (Sagamedia Indo Press, 2025)
Background: Pronunciation plays a crucial role in oral communication and classroom instruction, particularly in English as a Foreign Language (EFL) contexts where lecturers function as primary language models for students. Inaccurate pronunciation by lecturers may influence learners’ phonological awareness and speech production. Objective: This study aimed to analyze and compare pronunciation errors produced by an experienced English lecturer and a novice English lecturer, with a particular focus on consonant pronunciation in an EFL setting. Methods: This research employed a descriptive comparative case study design. Two English lecturers (one experienced and one novice) participated as cases. Data were collected through a pronunciation test consisting of 70 English words, read aloud by each participant and audio-recorded. Pronunciation accuracy was assessed based on a predetermined phonemic target using standard IPA transcription. Errors were identified and categorized according to consonant error types, and results were analyzed descriptively using frequency counts and error rates. Results: The findings revealed that the experienced lecturer produced 7 pronunciation errors out of 70 tokens (10.0%), while the novice lecturer produced 12 errors (17.1%). Common error patterns involved fricative and dental consonants, including substitutions such as /v/→/f/ and /θ/→/t/. Although both lecturers demonstrated generally acceptable pronunciation performance, the novice lecturer showed a higher frequency of consonant errors than the experienced lecturer. Conclusion: The study indicates that teaching experience may be associated with lower pronunciation error rates, particularly in consonant production. However, given the limited sample size, the findings should be interpreted cautiously. Further research with larger samples and more varied speech tasks is recommended to better understand pronunciation performance among EFL lecturers and its implications for language instruction.